(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research focuses on the role of innovation in enhancing competitiveness within the private sector in Saudi Arabia, with particular emphasis on the impact of innovation on company performance in terms of market share, financial performance, and sustainable growth. The study aims to explore the relationship between innovation and achieving competitive advantage, while highlighting the importance of supporting innovation policies as part of Saudi Arabia’s Vision 2030. The research employed a survey methodology to collect data from a representative sample of private sector companies operating across various industries in the Kingdom. The survey was designed to measure the extent to which these companies adopt innovative practices and to assess the impact of such practices on their operational and financial outcomes. The results revealed that companies investing in innovation and adopting policies that encourage innovative thinking are able to achieve higher levels of financial performance and increase their market share. Furthermore, the findings indicate that innovation is not merely a tool for product and service improvement, but a fundamental driver of sustainable growth in a rapidly changing competitive environment. The study emphasizes the need to enhance investments in research and development and to develop human capital to bolster innovation capabilities within companies. Additionally, the study highlights the importance of fostering collaboration between the public and private sectors and between academic institutions and companies to create a supportive environment for innovation. In conclusion, the research offers a set of practical recommendations aimed at fostering a culture of innovation within the private sector and ensuring the achievement of Vision 2030’s goals to transform Saudi Arabia into a knowledge-based economy.